2017
DOI: 10.3390/antibiotics6010009
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Assessment of Antibiotic Pan-Drug-Resistance in the UK: Bayesian Analysis of an Expert Elicitation Study

Abstract: To inform the UK antimicrobial resistance strategy, a risk assessment was undertaken of the likelihood, over a five-year time-frame, of the emergence and widespread dissemination of pan-drug-resistant (PDR) Gram-negative bacteria that would pose a major public health threat by compromising effective healthcare delivery. Subsequent impact over five- and 20-year time-frames was assessed in terms of morbidity and mortality attributable to PDR Gram-negative bacteraemia. A Bayesian approach, combining available dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Surprisingly, the incidence of infections by resistant bacteria was higher in countries with high use (ie, Portugal) compared with those with lower use (ie, Iceland or Norway) of antibiotics. Similarly, Carter et al 45 calculated the cost of infections produced by pandrug-resistant Gram-negative bacteria in the UK in an estimated 79 000 deaths over a 20-year period. With regard to the role of antibiotics on preventing complications, Babar-Craig et al 46 reported that complications requiring surgical intervention were similar in patients receiving antibiotic treatment or not.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the incidence of infections by resistant bacteria was higher in countries with high use (ie, Portugal) compared with those with lower use (ie, Iceland or Norway) of antibiotics. Similarly, Carter et al 45 calculated the cost of infections produced by pandrug-resistant Gram-negative bacteria in the UK in an estimated 79 000 deaths over a 20-year period. With regard to the role of antibiotics on preventing complications, Babar-Craig et al 46 reported that complications requiring surgical intervention were similar in patients receiving antibiotic treatment or not.…”
Section: Discussionmentioning
confidence: 99%
“…Kentucky strains might pose in the near future. A recent risk assessment study on Antibiotic Pan Drug Resistance (PDR) in the UK has estimated 284,000 cases of PDR Gram-negative bacteraemia leading to 79,000 deaths in a span of 20 years [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“… 15 Moreover, due to the abuse of broad-spectrum antibiotics in clinics and transfection of antibiotic resistance genes, the prevalence of PDR appears to be increasing. 29 , 30 PDR infections pose a great challenge to the current antibiotic management. Therefore, it is urgent to explore new antibiotics for PDR infections.…”
Section: Discussionmentioning
confidence: 99%